Roles of Macrophage Exosomes in Immune Response to Calcium Oxalate Monohydrate Crystals - Singhto, Nilubon; Kanlaya, Rattiyaporn; Nilnumkhum, Angkhana; Thongboonkerd, Visith (Frontiers in Immunology, 2018)
In kidney stone disease, macrophages secrete various mediators via classical secretory pathway and cause renal interstitial inflammation. However, whether their extracellular vesicles, particularly exosomes, are involved in kidney stone pathogenesis remained unknown. This study investigated alterations in exosomal proteome of U937-derived macrophages (by phorbol-12-myristate-13-acetate activation) after exposure to calcium oxalate monohydrate (COM) crystals for 16-h using 2-DE-based proteomics approach. Six significantly altered proteins in COM-treated exosomes were successfully identified by nanoLC-ESI-ETD MS/MS as proteins involved mainly in immune processes, including T-cell activation and homeostasis, Fcγ receptor-mediated phagocytosis, interferon-γ (IFN-γ) regulation, and cell migration/movement. The decreased heat shock protein 90-beta (HSP90β) and increased vimentin were confirmed by Western blotting. ELISA showed that the COM-treated macrophages produced greater level of interleukin-1β (IL-1β), one of the markers for inflammasome activation. Functional studies demonstrated that COM-treated exosomes enhanced monocyte and T-cell migration, monocyte activation and macrophage phagocytic activity, but on the other hand, reduced T-cell activation. In addition, COM-treated exosomes enhanced production of pro-inflammatory cytokine IL-8 by monocytes that could be restored to its basal level by small-interfering RNA (siRNA) targeting on vimentin (si-Vimentin). Moreover, si-Vimentin could also abolish effects of COM-treated exosomes on monocyte and T-cell migration as well as macrophage phagocytic activity. These findings provided some implications to the immune response during kidney stone pathogenesis via exosomal pathway of macrophages after exposure to COM crystals.